MENGENAL ASPERGILLOSIS, INFEKSI JAMUR GENUS ASPERGILLUS - Hasanah, Uswatun (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
Aspergillus is one of many fungi (fungi) that are widely used for research in the field of biotechnology, industry, and education. Aspergillus breeds with the formation of hyphae or buds and produces spore-forming conidophores. The spores are spread freely in the open air so that inhalation can not be avoided and enter through the respiratory tract into the lungs. Aspergillosis is a disease caused by Aspergillus fungus, a spectrum of human and animal diseases, the most common forms of allergic bronchopulmonary aspergillosis, pulmonary aspergilloma and invasive aspergillosis, also called brooder pneumonia, mycotic pneumonia, or pneumomycosis. Aspergillosis generally develops only in immunocompromised individuals, with an immunological reaction to this process. In general there are trigger antibodies (IgG) and in 50% of cases with positive skin test results of Aspergillus spp. Agents causing cosmopolitan aspergillosis, Aspergillus fumigatus intake, Aspergillus flavus, Aspergillus niger, Aspergillus nidulans and Aspergillus terreus. Aspergillosis is an opportunistic infection, most common in the lungs, and by Aspergillus fumigatus species, a fungus present in manure and humus. Spores of this species can be sucked into the lungs and cause chronic infection or disseminated aspergillosis, in case of invasive lung infections by Aspergillus. Bronchopulmonary aspergillosis can occur in people allergic to Aspergillus. Allergic bronchopulmonary aspergillosis patients have asthma and are treated with prednisolone to treat wheezing, and antifungal sounds (eg, itraconazole and amphoterizine) for treatment.